2014
DOI: 10.17547/kjsr.2014.22.3.139
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Mindfulness in the Relationship between Emotional Intelligence and Stress among Clinical Nurses

Abstract: The purpose of this study was to examine the mediating effects of mindfulness on the relationships between emotional intelligence and stress among nurses. Cross-sectional survey design was conducted. Data were collected using questionnaire from 151 nurses who working at a university hospital in Seoul. The survey instruments included Emotional intelligence (The Wong and Law EI Scale), Mindfulness (Mindfulness Scale) and Stress (Stress Response Inventory). Data were analyzed using Baron and Kenny's (1986) a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
2
4
1
Order By: Relevance
“…Thus, development of programs to prevent burnout resulting from work experience or position is vital. Conversely, nurses who were male, in their fifties, had a bachelor's degree, head nurses, and nurses with five or more years of working experience had greater mindfulness scores; this result was similar to that of Oh & Koh [1]. However, this topic should be the subject of detailed future investigation, since few studies have examined mindfulness in clinical nurses.…”
Section: ▪4 Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Thus, development of programs to prevent burnout resulting from work experience or position is vital. Conversely, nurses who were male, in their fifties, had a bachelor's degree, head nurses, and nurses with five or more years of working experience had greater mindfulness scores; this result was similar to that of Oh & Koh [1]. However, this topic should be the subject of detailed future investigation, since few studies have examined mindfulness in clinical nurses.…”
Section: ▪4 Discussionsupporting
confidence: 63%
“…A comparative study is required in order to examine this factor. The average mindfulness score, however, was 3.91, which was lower than that of another study on nurses, which reported an average score of 4.09 [1]. Mindfulness is known to improve individuals' ability to eliminate dysfunctional behavior patterns in stressful situations by reducing immediate emotional responses and promoting cognition evaluation [10].…”
Section: ▪4 Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The quality of clinical nurses' work environment is believed to affect quality of patient care, to a greater extent than that of a positive working attitude. However, it has been reported that nurses tend to experience more work-related stress compared with other occupations, due to growing demand for quality as well as quantity in medical services, and due to the complexity of maintaining relationships with people of varying professions [1]. This stress generates negative job attitudes among nurses, and affects quality of medical service, which subsequently increases the rate of nursing errors, decreases patient satisfaction [2], and causes symptoms of burnout among nurses.…”
Section: Introductionmentioning
confidence: 99%
“…In extant research nurse burnout has shown positive correlation with job stress and negative correlation with job satisfaction [4,5]. By contrast, mindfulness meditation is negatively correlated with job stress [1]. The purpose of this study is to investigate the effects of job stress, burnout, and mindfulness meditation on nurses' job satisfaction, and to obtain preliminary data regarding increasing job satisfaction of nurses.…”
Section: Introductionmentioning
confidence: 99%